2018
DOI: 10.1002/asia.201800493
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene (NHC)‐Organocatalyzed Kinetic Resolutions, Dynamic Kinetic Resolutions, and Desymmetrizations

Abstract: The last couple of decades have witnessed tremendous development within N-heterocyclic carbene (NHC) organocatalysis. NHCs have been used as powerful organic catalysts in asymmetric synthesis. Although great achievements have been made in asymmetric NHC catalysis, their applications in kinetic resolution (KR), dynamic kinetic resolution (DKR), and desymmetrization processes have been relatively less developed. Moreover, limited activation modes have been involved in these processes. This review provides an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(14 citation statements)
references
References 200 publications
0
13
0
Order By: Relevance
“…Organocatalytic strategies by N ‐heterocyclic carbene (NHC) catalysis represent a useful tool for the execution of a broad range of asymmetric transformations including benzoin‐type condensations, Stetter reactions, hydroacylations, annulations, and cycloadditions These processes proceed by normal polarity or umpolung reactivity through well‐established activation modes involving key reactive species, namely the Breslow intermediate, homoenolate, and azolium (di)enolate intermediates (Scheme a) . Additionally, the synthetic opportunities given by NHC organocatalysts are further expanded by the application of redox protocols (internal and external oxidation strategies) leading to the acyl azolium intermediate for the acylation of oxygen‐, sulfur‐, and nitrogen‐nucleophiles in challenging kinetic resolution (KR), macrolactonization, desymmetrization,, and polymerization processes. In particular, the N ‐acylation reaction using aldehydes as acylating agents in place of carboxylic acids/derivatives has proven to possess some practical advantages (mild reaction conditions, chemoselectivity, no need of coupling reagents) and it has been successfully applied to the functionalization of alkylamines, anilines, amides, sulfoximines, azomethine imines, and several nitrogen‐containing heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Organocatalytic strategies by N ‐heterocyclic carbene (NHC) catalysis represent a useful tool for the execution of a broad range of asymmetric transformations including benzoin‐type condensations, Stetter reactions, hydroacylations, annulations, and cycloadditions These processes proceed by normal polarity or umpolung reactivity through well‐established activation modes involving key reactive species, namely the Breslow intermediate, homoenolate, and azolium (di)enolate intermediates (Scheme a) . Additionally, the synthetic opportunities given by NHC organocatalysts are further expanded by the application of redox protocols (internal and external oxidation strategies) leading to the acyl azolium intermediate for the acylation of oxygen‐, sulfur‐, and nitrogen‐nucleophiles in challenging kinetic resolution (KR), macrolactonization, desymmetrization,, and polymerization processes. In particular, the N ‐acylation reaction using aldehydes as acylating agents in place of carboxylic acids/derivatives has proven to possess some practical advantages (mild reaction conditions, chemoselectivity, no need of coupling reagents) and it has been successfully applied to the functionalization of alkylamines, anilines, amides, sulfoximines, azomethine imines, and several nitrogen‐containing heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] We are interested in exploring N-heterocyclic carbenes (NHCs) as key organic catalysts for new activations and enantioselective reactions.I nt he past, NHCs were mostly used to activate carbon atoms (Scheme 1a). [14][15][16][17][18][19][20][21][22][23][24][25][26] Thec arbon atoms were activated as either nucleophilic or electrophilic reactive centers.I n2 017, Chi and co-workers found that through the addition of ac arbene to the aldehyde moiety of a2 -hydroxyl benzaldehyde under oxidative conditions,t he phenol oxygen atom could be activated for enantioselective reactions. [27] This activation converted the acylazolium to an ortho-quinone methide (o-QM) intermediate with the oxygen as the reactive center (Scheme 1b,l eft).…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in exploring N‐heterocyclic carbenes (NHCs) as key organic catalysts for new activations and enantioselective reactions. In the past, NHCs were mostly used to activate carbon atoms (Scheme a) . The carbon atoms were activated as either nucleophilic or electrophilic reactive centers.…”
Section: Introductionmentioning
confidence: 99%